Employee satisfaction regarding pay, financial rewards and fringe benefits at XYZ Resort Hotel in Kuching - Ch'ng, Lay Kean (Universiti Malaysia Sarawak, (UNIMAS), 1997)
This paper is about employee satisfaction with regards to pay, financial rewards and fringe benefits among rank and file workers at XYZ Resort Hotel in Kuching. This study examined employee satisfaction and the influence of socio-demographic characteristics on employee satisfaction with regards to pay, financial rewards and fringe benefits. The study also attempted to determine intercorrelation of pay satisfaction dimensions such as pay level, pay raise, benefits, pay structure and administration. For the research, about 30% of the rank and file workers who had at least one year of employment in the organisation were interviewed using a set of questionnaires. Six kinds of financial rewards included in this study are meal allowance, overtime pay, shift allowance, service charge, annual incentive and other individual incentives. Nine types of fringe benefits included in this study are the long service award, staff quarters, staff transportation, uniform, laundry service, medical fees, EPF contribution, SOCSO compensation and paid leave. Some of the significant findings of this study shows that: (1) employees are dissatisfied with pay and all types of financial rewards being provided; (2) however, employees are only dissatisfied with certain types of fringe benefits such as long service award, staff quarters, staff transportation and uniform; (3) certain demographic characteristics have influenced employee satisfaction with regards to pay, financial rewards and fringe benefits; and (4) some of the pay satisfaction dimensions are highly correlated.